2006
DOI: 10.1111/j.1530-0277.2006.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the Association Between Alcohol Consumption and Depression Depend on How They Are Measured?

Abstract: The results of the present study suggest that measurement and gender are key issues in interpreting findings on the relationship between alcohol and depression. First, depression is primarily related to drinking larger quantities per occasion, less related to volume, and unrelated to drinking frequency, and this effect is stronger for women than for men. Second, the overall relationship between depression and alcohol consumption is stronger for women than for men only when depression is measured as meeting a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
136
7
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 35 publications
(66 reference statements)
14
136
7
9
Order By: Relevance
“…A meta-analysis found that a higher proportion of people diagnosed with alcohol dependence also suffers comorbid mental health conditions than people who suffer a mental health condition and are also alcohol-dependent (Jane-Lopis & Matytsina 2006). In a population-based survey, Graham et al (2007) found no data to support the notion that light to moderate drinking (defined by low frequency or low volume) protects against major depression.…”
Section: Depressionmentioning
confidence: 85%
See 1 more Smart Citation
“…A meta-analysis found that a higher proportion of people diagnosed with alcohol dependence also suffers comorbid mental health conditions than people who suffer a mental health condition and are also alcohol-dependent (Jane-Lopis & Matytsina 2006). In a population-based survey, Graham et al (2007) found no data to support the notion that light to moderate drinking (defined by low frequency or low volume) protects against major depression.…”
Section: Depressionmentioning
confidence: 85%
“…This may in part be due to the manner in which both consumption and depression are measured (Graham et al 2007). In a longitudinal study, Haynes et al (2005) found that excessive alcohol consumption was not associated with the onset of anxiety and depression, but that abstinence was associated with lower depressive risks.…”
Section: Depressionmentioning
confidence: 99%
“…A cohort of young people was assessed in 1992 (T1), 1994 (T2), 1999 (T3) and 2005 (T4). The T1 survey comprised students attending junior high school (grades 8-10) and senior high school (grades [11][12][13], and the sample was selected to yield a national representative cross-section of this student population (response rate: 97%). At T2, students who were still in their original school filled in questionnaires in the classroom -as they did at T1.…”
Section: Methodsmentioning
confidence: 99%
“…Obviously, such research may be of clinical significance, yet the findings do not necessarily apply to mild forms of emotional distress and non-pathological drinking [13]. To address subclinical conditions is important in its own right, not least because they may contribute to the total burden of harm and social cost at least as much as the clinical ones -simply by being far more prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…It has been validated for use in alcohol related studies both in the developed world and in Nigeria and a score of 5 is considered a good cut off point to indicate the presence of AUD in a patient [14][15][16][17]. The Beck's Depression Inventory (BDI) is a questionnaire comprising 21 items [18].…”
Section: Instrumentsmentioning
confidence: 99%